2018
DOI: 10.1177/1054773818790007
|View full text |Cite
|
Sign up to set email alerts
|

Format of Parent Education Material Preferred by New Mothers

Abstract: A descriptive cohort study to determine new mothers' preferred modality for educational materials, and if the format impacted the mothers' perception of an evidenced-based practice safe sleep program. The sample included new mothers anticipating discharge from a mother-baby unit with their newborn. Participants responded to a four-item survey administered by a research assistant. Respondents' self-reported preferred format for patient education was technology-based materials in both cohorts. The video teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Parents want coherent and personalized services regarding infant sleep issues, and health practitioners involved in follow-up services need to cooperate in the design of appropriate programs. Different sources of information can be used by different participants or technological platforms [ 91 ]. It seems important that professionals and stakeholders within each country come together to develop a common approach about when, what, and how to communicate important sleep-related knowledge to new families.…”
Section: Discussionmentioning
confidence: 99%
“…Parents want coherent and personalized services regarding infant sleep issues, and health practitioners involved in follow-up services need to cooperate in the design of appropriate programs. Different sources of information can be used by different participants or technological platforms [ 91 ]. It seems important that professionals and stakeholders within each country come together to develop a common approach about when, what, and how to communicate important sleep-related knowledge to new families.…”
Section: Discussionmentioning
confidence: 99%
“…7 In related healthcare areas, it has been shown that patients can improve collection techniques by video instruction. [21][22][23][24] An effective learning environment and the sharing of information is of importance to support patient-centred care. 19 Our results also indicate that the education has to offer diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, where dried blood spots were collected in a child population, incomplete sampling was related to improper training 7 . In related healthcare areas, it has been shown that patients can improve collection techniques by video instruction 21‐24 . An effective learning environment and the sharing of information is of importance to support patient‐centred care 19 .…”
Section: Discussionmentioning
confidence: 99%